2021
DOI: 10.3390/ani11061557
|View full text |Cite
|
Sign up to set email alerts
|

Application of Genomic Data for Reliability Improvement of Pig Breeding Value Estimates

Abstract: Replacement pigs’ genomic prediction for reproduction (total number and born alive piglets in the first parity), meat, fatness and growth traits (muscle depth, days to 100 kg and backfat thickness over 6–7 rib) was tested using single-step genomic best linear unbiased prediction ssGBLUP methodology. These traits were selected as the most economically significant and different in terms of heritability. The heritability for meat, fatness and growth traits varied from 0.17 to 0.39 and for reproduction traits from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…The increase in the average reliability of EBVs is probably a consequence of the increased volume of information included in the joint evaluation, as reported in the research of many authors [ 18 , 36 , 37 , 38 ]. The reliability of the EBVs for the NBA was much higher than in [ 39 ]. These authors reported much lower values for the reliability of EBVs in highly prolific sows, i.e., 0.33 for the NBA compared to 0.74 recorded in our study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The increase in the average reliability of EBVs is probably a consequence of the increased volume of information included in the joint evaluation, as reported in the research of many authors [ 18 , 36 , 37 , 38 ]. The reliability of the EBVs for the NBA was much higher than in [ 39 ]. These authors reported much lower values for the reliability of EBVs in highly prolific sows, i.e., 0.33 for the NBA compared to 0.74 recorded in our study.…”
Section: Discussionmentioning
confidence: 67%
“…These authors reported much lower values for the reliability of EBVs in highly prolific sows, i.e., 0.33 for the NBA compared to 0.74 recorded in our study. Even though the data on pedigree and own phenotype were used in both studies, the sample was much smaller in the estimation of BV in the mentioned study [ 39 ], which can be related to the amount of information in the pedigree file and the smaller volume of data on phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous article, we discussed the increase in the accuracy of breeding value estimates by including genomic data on the characteristics of meat and fattening productivity and reproduction traits in pigs [39]. However, in this study, we decided to evaluate the validity of the procedure application for individual SNP marker effect weighting and compared the obtained estimates' reliability with traditional BLUP AM (Scenario 4) and ssGBLUP (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…This problem can be overcome by using genetic data to improve the reliability of breeding value estimates for dogs in the bonitation process. Information at the DNA level may lead to faster genetic improvement than relying on phenotypic data and pedigrees alone [15]…”
Section: Introductionmentioning
confidence: 99%